Intestinal hypomagnesemia-two cases of recurrent seizures: a diagnostic odyssey - Soodhana, Dhanya; Anirudhan, Deepa; Krishnanunni, Sudha; Pachat, Divya; Nayar, Lathika; Menon, Janaki (International Journal of Contemporary Pediatrics, 2024)
Familial hypomagnesemia with secondary hypocalcemia (FHSH) is a rare autosomal recessive disorder that is manifested as severe hypomagnesemia and moderate to severe hypocalcemia. Affected children present with refractory seizures in infancy. It results from mutations in the gene encoding transient receptor potential cation channel member 6 (TRPM6) on chromosome 9q22. The primary defect is impaired intestinal absorption of magnesium with secondary defect in the renal conservation of magnesium. We report two infants who presented with refractory seizures beginning in the first three months of life, the clinical phenotype of both these children was normal. Both were diagnosed to have hypocalcemic seizures. The children were managed with intravenous calcium and magnesium during their hospital stay, however were discharged on calcium supplementation alone. As they continued to have seizures inspite of good compliance to medications and in view of persistently low magnesium levels, hypomagnesemia as a cause of seizures was considered. Genetic evaluation revealed variants in the TRPM6 gene in both the cases The seizures were brought under control once the magnesium levels were normalized. A possibility of hypomagnesemia with secondary hypocalcemia should be thought of in any case of refractory hypocalcemia and inappropriately low levels of parathyroid hormone (PTH) The purpose of this series is to highlight the importance of systematically working up children with inherited hypomagnesemia.